2013
DOI: 10.1021/ac4016159
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Assisted Selective Preconcentration in a Straight Nanochannel

Abstract: We investigate the preconcentration profiles of a fluorescein and bovine serum albumin derivatized with this fluorescent tag in a microfluidic chip bearing a nanoslit. A new preconcentration method in which a hydrodynamic pressure is added to both electroosmotic and electrophoretic contributions is proposed to monitor the location of the preconcentration frontline. A simple predictive model of this pressure-assisted electropreconcentration is proposed for the evolution of the flow profile along this micro/nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…The unbalanced ionic transport between anionic and cationic species through a nanofluidic structures initiates a polarization effect related to the concentration domain, which can be applied for focusing and locally preconcentrate ionic species. [12], [13] Compared to the classical microfluidic field, the nanometer dimension of the channel requires specific theoretical predictions and experimental discussions. [14], [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…The unbalanced ionic transport between anionic and cationic species through a nanofluidic structures initiates a polarization effect related to the concentration domain, which can be applied for focusing and locally preconcentrate ionic species. [12], [13] Compared to the classical microfluidic field, the nanometer dimension of the channel requires specific theoretical predictions and experimental discussions. [14], [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…This is of practical significance as gradients in binary electrolyte are observed during FASS and concentration polarization at the interface of a microchannel and nanochannel [13]. The latter phenomenon has found applications in shockelectrodialysis for deionization of water [10].…”
Section: (A) Electromigration In Binary Electrolytesmentioning
confidence: 96%
“…Stability of the depletion or concentration zones for as long as possible means increased enhancement factors. Louer et al demonstrated the use of external hydrodynamic pressure to achieve concentration on the anodic or cathodic side of the NMI using the same device design and demonstrated stable ICP . The 150‐nm nanochannels were made in glass.…”
Section: Stackingmentioning
confidence: 99%